Estudo genotóxico e carcinogênico da exposição ao pó de cromo trivalente em Rattus norvegicus - Leal, Samira Rêgo Martins de Deus (2017)
Chromium-like metals are naturally occurring elements and in view of their multiple industrial, domestic, agricultural, medical and technological applications have led to their widespread distribution, raising concerns about their potential effects on human health and environment. OBJECTIVE: To evaluate the possible genotoxic and carcinogenic effects of exposure of male Rattus norvegicus to atmospheric trivalent chromium powder. METHODS: Male Rattus norvegicus were divided into acute exposure groups (250 and 500 μg/m3 for 8h, n=5/group) and subchronic (500 μg/m3, 1h30min/day for 45 days, n=8/group) to atmospheric trivalent chromium powder. As negative control group, animals were treated with dH2O 10 mL/kg (acute exposure) and exposed to filtered air (subchronic exposure); and as a positive, animals treated with cyclophosphamide 50 mg/kg, i.p. (acute exposure). At the end of the acute treatment, the comet assay was performed in peripheral blood and tests of micronuclei and chromosomal aberrations in bone marrow. At the end of the subchronic exposure period, histopathological analyzes of the pulmonary and hepatic tissues were performed. RESULTS: Acute exposure to trivalent chromium powder (250 and 500 μg/m3) induced (p<0.05) genotoxic damage to rat lymphocyte DNA by analysis of % of DNA in the tail, tail length and TailMoment. Mutagenic effects were also evidenced by the elevation of the micronucleus frequency in polychromatic erythrocytes, only for the group exposed to 500 μg/m3, compared to the negative control. In addition, acute treatment (500 μg/m3) induced a prominent increase in the number of chromosomal aberrations, especially dicentric chromosomes, chromosomal rings and chromosome fragments, compared to the non-exposed group. Histopathological analyzes of the subchronic exposed group revealed in the lung tissue metaplasia and epithelial desquamation in the bronchi and alveoli, accompanied by a focus of inflammatory activity in the alveoli and formation of granulomas. In hepatic tissue, mild or moderate hepatocyte lesions were observed, showing leukocyte infiltration, hydropic degeneration and/or necrosis and apoptotic hepatocytes. CONCLUSION: The data from the present study prove that exposure to atmospheric trivalent chromium powder may induce genotoxic events to cellular DNA, which in turn provoke genomic instability, which are determinant for the carcinogenesis processes.